APPROACH TO HOMELESSNESS VULNERABILITY AND THE IMPACT AS ONE HEALTH INITIATIVE - Gravinatti, Mara Lucia; Timenetsky, Jorge; Biondo, Alexander Welker (Archives of Veterinary Science, 2017)
Homeless has been considered a worldwide public policy problem and may demand a multi-professional intervention with social assistance and health care approaches. Some of these homeless may have close and companion interactions with domestic animals in their environment. Although pets may provide emotional stability, may also contribute to human sheltering refusal and homeless persistence, as pets may not be allowed on most human shelters. Pet presence and environmental exposure may aggravate co-infections in such vulnerable population. Therefore, veterinarian inclusion in such network care frame has been crucial to insure animal health and reduce zoonosis and related risk factor.